Frequency of ESBL in Surgical Site Infection at a Tertiary Care Hospital - Islam, M Saiful; Yusuf, M Abdullah; Islam, M Badrul; Jahan, Waseka Akhter (Journal of Current and Advance Medical Research, 2014)
Background: Infection caused by ESBL in the surgical site infection is very alarming. Objective: The purpose of the present study was to see the status of ESBL bacteria isolated from surgical site infection with their antimicrobial sensitivity pattern. Methodology: This cross sectional study was conducted in the Department of Microbiology at Dhaka Medical College, Dhaka from January, 2005 to December, 2005 for a period of one (1) year. All the patients presented with surgical site infections at any age with both sexes were included a study population. Detection of extended spectrum beta lactamase producing Gram negative bacteria was done by using disc diffusion method and was confirmed by E- test ESBL method. Sensitivity pattern of ESBL producers were observed against quinolone and fluoroquinolones. ESBLs are the enzymes capable of hydrolyzing all penicillin, monobactam and cephalosporins except cephamycin, but inactive against imipenem. Result: A total number of 92 surgical wound samples were collected of which 68(73.9%) samples were culture positive. Interestingly, most of the E. coli was ESBL positive (55.0%). Klebsiella species was 33.1% ESBL positive. ESBL positivity of Proteus and Pseudomonas species were low (11.1%). Among the isolated Pseudomonas species, 1(6.67%) of the 15 strains isolated from wound swab was ESBL producers. ESBL positivity was significantly found in surgically wound samples (p=0.0001). Among the ESBL producers, all the E. coli, Klebsiella species, Proteus species and Pseudomonas species were resistant to amoxicillin, cephradine, ceftriaxone, aztreonam, ceftazidime and cefotaxime. All the Gram negative bacteria were sensitive to imipenam. Conclusion: A considerable numbers of ESBL producing bacteria were detected from surgical wound. DOI: http://dx.doi.org/10.3329/jcamr.v1i2.20514 Journal of Current and Advance Medical Research Vol.1(2) 2014: 25-29